2020
DOI: 10.1002/cssc.202001114
|View full text |Cite
|
Sign up to set email alerts
|

Dialing in Direct Air Capture of CO2 by Crystal Engineering of Bisiminoguanidines

Abstract: Direct air capture (DAC) technologies that extract carbon dioxide directly from the atmosphere using chemical processes have the potential to achieve zero or negative emissions and restore the atmospheric composition to an optimal level with respect to the CO2 concentration. However, before such technologies can be developed and applied energy-efficiently, we need to gain fundamental understanding of DAC chemistry. Here we report a structure-properties relationship study of DAC by crystallization of bis-iminog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…Nevertheless, the temperatures of regeneration are very similar for GBIG, MGBIG, and DABIG, in the range of 120 to 160 C (under a ow of air). 10 Outstanding challenges and future opportunities With its structural precision and the prospect for tuning the CO 2 binding, transport, and release in crystalline frameworks, crystal engineering of MOFs and HBFs offers unique opportunities for DAC. Table 1 summarizes the key properties for some of these materials, relevant to their DAC performance.…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the temperatures of regeneration are very similar for GBIG, MGBIG, and DABIG, in the range of 120 to 160 C (under a ow of air). 10 Outstanding challenges and future opportunities With its structural precision and the prospect for tuning the CO 2 binding, transport, and release in crystalline frameworks, crystal engineering of MOFs and HBFs offers unique opportunities for DAC. Table 1 summarizes the key properties for some of these materials, relevant to their DAC performance.…”
Section: +mentioning
confidence: 99%
“…Indeed, simple thermodynamic considerations define the lower end of the CO 2 binding constant (log K ) to 3.7, corresponding to a free energy of binding of at least −21 kJ mol −1 . 10 Furthermore, considering the entropy of binding is typically negative, the enthalpy of CO 2 binding needs to be significantly exothermic (at least −50 kJ mol −1 ). With regard to selectivity, DAC sorbents need to be selective for CO 2 against water, which is 10–100 times more abundant than CO 2 in the atmosphere and tends to bind relatively strongly to most sorbents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported an innovative iminoguanidine type sorbent, namely 2,6-pyridine-bis(iminoguanidine) (PyBIG) which could capture CO 2 from ambient air, crystallize as an insoluble carbonate and regenerate PyBIG by mild heating with concomitant CO 2 releasing ( Seipp et al., 2017 ; Brethomé et al., 2018 ). Soon after, they disclosed another simple and robust iminoguanidine compound called glyoxal-bis(iminoguanidine) (GBIG), by which the flue gas CO 2 absorption led to the formation of a dehydrated bicarbonate salt ( Williams et al., 2019 ; Garrabrant et al., 2019 ); however, further results proved that the GBIG was ineffective for DAC ( Custelcean et al., 2020 ). In addition, their most recent structure-property relationship study of GBIG, MGBIG (methylglyoxal-bis(iminoguanidine)) and DABIG (diacetyl-bis(iminoguanidine)) revealed that minor modifications in the molecular structures would result in dramatic differences in the crystal structures, aqueous solubilities, conformational flexibilities, as well as free energies for CO 2 absorption ( Custelcean et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Soon after, they disclosed another simple and robust iminoguanidine compound called glyoxal-bis(iminoguanidine) (GBIG), by which the flue gas CO 2 absorption led to the formation of a dehydrated bicarbonate salt ( Williams et al., 2019 ; Garrabrant et al., 2019 ); however, further results proved that the GBIG was ineffective for DAC ( Custelcean et al., 2020 ). In addition, their most recent structure-property relationship study of GBIG, MGBIG (methylglyoxal-bis(iminoguanidine)) and DABIG (diacetyl-bis(iminoguanidine)) revealed that minor modifications in the molecular structures would result in dramatic differences in the crystal structures, aqueous solubilities, conformational flexibilities, as well as free energies for CO 2 absorption ( Custelcean et al., 2020 ). Although great progress has been made, the development of DAC sorbents for CO 2 capture is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%